PENGARUH EDUKASI TERSTRUKTUR TERHADAP KEPATUHAN PENGGUNAAN MASKER PEDAGANG PASAR PANORAMA KOTA BENGKULU SEBAGAI UPAYA PENCEGAHAN COVID-19 - Bayu Ilham G; Septiyanti Septiyanti; Andra Saferi Wijaya (Poltekkes Kemenkes Bengkulu, 2021)
Abstract: Covid 19 is an infectious disease caused by a new type of corona virus, the number of confirmed cases of the corona virus in the world is 26.76 million cases. Of these, there have been 877,886 deaths and 18.8 million cases of patients who have been declared cured. Data obtained from the Ministry of Health of the Republic of Indonesia stated that Bengkulu Province had 11,197 cases with the highest number of deaths as many as 56 people. This type of research is quantitative research, with a quasi-experimental research design (quasi-experimental) using a pretest-posttest research design with a control group. The sample is all Bengkulu City panoramic market traders who have WhatsApp. The sampling technique used in this study is a purposive sampling technique, namely one sampling non-random sampling technique. The results of this study indicate that there is an influence of the influence of structured education on the level of compliance with the use of masks at the Panorama Market traders in Bengkulu City as an effort to prevent COVID-19. Wilcoxon statistical test results in the intervention group showed a p value of 0.001 (p value 0.05) while the control group showed a p value of 0.001 (p value 0.05). Education on the use of masks is beneficial for traders as an effort to prevent Covid-19. Structured education on the use of masks is expected to continue to be active as a program to prevent the transmission of Covid-19.